SARS-CoV-2 membrane protein induces neurodegeneration via affecting Golgi-mitochondria interaction - Fang Wang; Hailong Han; Caifang Wang; Jingfei Wang; Yanni Peng; Ye Chen; Yaohui He; Zhouyang Deng; Fang Li; Yikang Rong; Danling Wang; Wen Liu; et al. (Translational Neurodegeneration)
Abstract Background Neurological complications are a significant concern of Coronavirus Disease 2019 (COVID-19). However, the pathogenic mechanism of neurological symptoms associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is poorly understood. Methods We used Drosophila as a model to systematically analyze SARS-CoV-2 genes encoding structural and accessory proteins and identified the membrane protein (M) that disrupted mitochondrial functions in vivo. The M protein was stereotaxically injected to further assess its effects in the brains of wild-type (WT) and 5 × FAD mice. Omics technologies, including RNA sequencing and interactome analysis, were performed to explore the mechanisms of the effects of M protein both in vitro and in vivo. Results Systematic analysis of SARS-CoV-2 structural and accessory proteins in Drosophila identified that the M protein induces mitochondrial fragmentation and dysfunction, leading to reduced ATP production, ROS overproduction, and eventually cell death in the indirect flight muscles. In WT mice, M caused hippocampal atrophy, neural apoptosis, glial activation, and mitochondrial damage. These changes were further aggravated in 5 × FAD mice. M was localized to the Golgi apparatus and genetically interacted with four wheel drive (FWD, a Drosophila homolog of mammalian PI4KIIIβ) to regulate Golgi functions in flies. Fwd RNAi, but not PI4KIIIα RNAi, reversed the M-induced Golgi abnormality, mitochondrial fragmentation, and ATP reduction. Inhibition of PI4KIIIβ activity suppressed the M-induced neuronal cell death. Therefore, M induced mitochondrial fragmentation and apoptosis likely through disruption of Golgi-derived PI(4)P-containing vesicles. Conclusions M disturbs the distribution and function of Golgi, leading to mitochondrial abnormality and eventually neurodegeneration via a PI4KIIIβ-mediated mechanism. This study reveals a potential mechanism for COVID-19 neurological symptoms and opens a new avenue for development of therapeutic strategies targeting SARS-CoV-2 M or mitochondria.